Analisis Keefektifan Penilaian Formatif Berbantuan Media Oodlu Pada Pembelajaran Ppkn Di SD - Puspita Sari, Rissa (EDUPEDIA Publisher, 2023)
In the Revolutionary Era 4.0, PPkn is learning that can build digital ethics for every student as the young generation of the Indonesian nation. With the sophistication of technology today, E-Learning has become a new idea in the process of teaching and learning activities. To achieve the desired learning objectives, evaluation activities are needed. One form of evaluation that can be carried out by educators is formative assessment activities. The effectiveness of formative assessment will greatly assist the assessment of educators. Therefore, in the process of its activities, it is very necessary to pay attention. Choosing the right learning media will make students more enthusiastic about learning. Serious games are an alternative for creating interesting learning activities. One type of Serious game learning media is the Oodlu application. This study used the literature study method, this article was reviewed with the aim of finding out how effective formative assessment assisted by Oodlu media is in teaching Civics in Elementary Schools. The research results of this article show that the Oodlu application is effectively applied in the formative assessment of Civics learning in elementary schools.